Focusing on claudin-5: A promising candidate in the regulation of BBB to treat ischemic stroke - Lv, Jianjun; Hu, Wei; Yang, Zhi; Li, Tian; Jiang, Shuai; Ma, Zhiqiang; Chen, Fulin; Yang, Yang (Progress in neurobiology, 2018)
Claudin-5 is a tight junction (TJ) protein in the blood-brain barrier (BBB) that has recently attracted increased attention. Numerous studies have demonstrated that claudin-5 regulates the integrity and permeability of the BBB. Increased claudin-5 expression plays a neuroprotective role in neurological diseases, particularly in cerebral ischemic stroke. Moreover, claudin-5 might be a potential marker for early hemorrhagic transformation detection in ischemic stroke. In light of the distinctive effects of claudin-5 on the nervous system, we present the elaborate network of roles that claudin-5 plays in ischemic stroke. In this review, we first introduce basic knowledge regarding the BBB and the claudin family, the characterization and regulation of claudin-5, and association between claudin-5 and other TJ proteins. Subsequently, we describe BBB dysfunction and neuron-specific drivers of pathogenesis of ischemic stroke, including inflammatory disequilibrium and oxidative stress. Furthermore, we summarize promising ischemic stroke treatments that target the BBB via claudin-5, including modified rt-PA therapy, pharmacotherapy, hormone treatment, receptor-targeted therapy, gene therapy, and physical therapy. This review highlights recent advances and provides a comprehensive summary of claudin-5 in the regulation of the BBB and may be helpful for drug design and clinical therapy for treatment of ischemic stroke.